Art and Culture Patronage in Lithuania: Impact on Culture, Business, and Society - Sabonytė, Rugilė; Jurėnienė, Virginija (Vilnius University Proceedings, 2025)
Art patronage has traditionally been considered a philanthropic act that supports cultural and artistic expression. This paper explores how modern art patronage has evolved into diverse models such as venture philanthropy, crowdfunding, and impact investment, while reflecting broader changes in social values, business interests, and public policies. Using Lithuania as a case study, we analyse historical and emerging patronage practices and their effects on culture, business, and society. The article integrates theoretical and empirical insights and incorporates new perspectives from cultural policy and altruism studies. Particular attention is given to motivations behind giving, the evolving role of the patron, and how strategic patronage can create social value in a time of public funding decline. This research contributes to understanding patronage’s potential to balance economic rationality and cultural sustainability.